PARLIAMENTARY REPRESENTATION OF NATIONAL MINORITIES IN SERBIA AND HUNGARY: MECHANISM FOR EFFECTIVE PARTICIPATION OF MINORITIES, OR TOOL FOR POLITICAL MANIPULATION? - Korhecz, Tamas (Pravni zapisi, 2022)
In multiethnic states, in which numerically large national, ethnic or linguistic minorities exist with a strong distinct identity, the principle of democracy requires that these groups have representatives in parliaments. However, in many multiethnic states the national-ethnic majority makes efforts to exclude or minimize the representation of minority national-ethnic groups in legislative bodies. Serbia and Hungary are nation states with relatively high percentage of citizens belonging to national-ethnic minorities, and with developed systems of the protection of minority rights. Both states enacted electoral laws facilitating the representation of national minorities in highest elected state bodies. This article describes, critically analyzes and compares the electoral rules and their practical implementation in both states, in order to answer the question whether these rules make it efficiently possible for national minorities to acquire proper representation in parliament. In order to answer this question, the results and experiences of the latest parliamentary elections – organized in 2022 in both states – will be elaborated as well.